Şeyhülislâm Abdürrahim Efendi’nin fetvaları ışığında XVIII. yüzyılda Osmanlı’da hukukî hayat - Cihan, Ravza (My University, 2016)
ŞEYHÜLİSLÂM ABDÜRRAHİM EFENDİ’NİN FETVALARI IŞIĞINDA XVIII. YÜZYILDA OSMANLI'DA HUKUKÎ HAYAT İslam fıkhının hem bilgi hem de yürürlük kaynağı olan fetvalar, fıkıh-toplum ilişkisine dair en mühim kaynağı teşkil etmektedir. Fetvâ-yı Şerîfe olarak tavsîf edilen şeyhülislâm fetvaları ise, sâir fetvalar arasında, değer ve bağlayıcılık açısından en üst sırada yer almaktadır. Osmanlı Devleti'nin yetmiş yedinci şeyhülislâmı olarak kayıtlara geçen Menteşizâde Abdürrahim Efendi, günümüze en fazla fetvası nakledilen şeyhülislâmdır. XVIII. yüzyılın ilk çeyreğine tekâbül eden görev süresi içerisinde kendisine yöneltilen suâllere verdiği fetvalar Fetâvâ-yı Abdürrahim olarak isimlendirilen derlemede bir araya getirilmiştir. Bu çalışmada Fetâvâ-yı Abdürrahim'den hareketle, XVIII. yüzyılın başlarında Osmanlı Devleti'nin hukukî hayatının alt dallarından arazi ve vergi düzeni ele alınmaktadır. Bu tez ile fıkhın, iktisadi ve sosyal hayat ile münâsebetini ve şeyhülislâmın dönemin meselelerinin çözümündeki rolünü araştırmak hedeflenmektedir. XVIII. yüzyıl, Fetâvâ-yı Abdürrahim, Arazi, Vergi

THE LEGAL LIFE IN THE OTTOMAN IN EIGHTEENTH CENTURY IN THE LIGHT OF ABD AL-RAHIM’S FATWAS The fatwas, which is both source of information and force of Islamic jurisprudence are the most important sources that indicate the relationship between Islamic jurisprudence and society. The fatwas of Shaykh al-Islam which called al-fatawa al-shareefah precede among other fatwas in terms of value and bindingness. Shaykh al-Islam Abd al-rahim who ise the seventy seventh shaykh al-Islam of Ottoman Empire is a shaykh al-Islam whose fatwas are the most transferred fatwas to today. The fatwas, given as answers to the questions asked him during his period of office which correspondes to the first quarter of the XVIIIth century, were collected in a compilation called al-Fatawa Abd al-rahim. In this study, layout of land and tax which are the subbranch of legal life of the Ottoman Empire in the early part of XVIIIth century were handled based on al-Fatawa Abd al-rahim. This dissertation aims to research the relationship between Islamic jurisprudence and socio-economic life of Ottoman, and the role of Shaykh al-Islam in resolving the problems of his period. XVIII. century , al-Fatawa Abd al-rahim, Land, Tax
Keywords: Fetvalar; Hukuk; İslam; İslâm; Tarih